Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø© Ø¹Ù† Ø§Ù„ÙØªÙˆÙ‰ Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© Ø¨ÙŠÙ† Ø¥Ù†Ø¯ÙˆÙ†Ø³ÙŠØ§ ÙˆÙ…Ø§Ù„ÙŠØ²ÙŠØ§ - Qonytha, Didin (Fakultas Syariah, 2014)
The discussion in this paper are the polemics of misyâr marriage that developed in the Bay State. This marriage is a marriage where a spouse has waived such right answer or do not earn a living and residence. The purpose to make the wedding the husband is free from obligation toward his wife to provide a living and residence as another wife.